Procedimentos analíticos para preparo de amostras de leite com ênfase à determinação de Ca e Mg por espectrometria de absorção atômica por chama - Dutra, Mauro José Alves (2004)
The present work had as objective the development of analytical procedures when preparing milk samples, emphasizing the determination of calcium and magnesium by spectrometry of atomlc absortion by flame. These procedures were based on the use of microwaves irradiation, the dilution and the direct sampling with Solutions containing amino mixtures. Such procedures had been compared with the conventional method. The investigated parameters for optimizing the digestion of milk samples by microwaves irradiation, using closed bottles under high pressure and a digestive mixture containing concentrated nitric acid (2,0 mL) and hydrogenperoxide 30% (m.v'1) 1,0 mL, were: volume variation of the milk sample (0,5 to 2,5 mL) and time of microwaves performance (4 to 20 min). From the volume analysis of the milk samples, the best volume was 0,5 mL, which supplies a limpid digested solution without fatty globules and with better results in the determination of calcium and magnesium. Considering the time of microwaves performance, the best result correspond to the P3 program, which has a total duration time of 12 minutes (intervals of 3 minutes) and the power variation from 0 to 650 W (intervals of 250 W). Considering the direct sampling of suspensions with the amino Solutions -Monoetanolamine (MEA) and Trishidroximetilaminometane (TRIS) + citric acid - various situations were investigated, varying the molar concentration of MEA and TRIS, remaining constant the molar concentration of citric acid. To analyze the influence of the citric acid, the molar concentration of amino MEA and TRIS remained constant, varying the molar concentration of the citric acid. Amino MEA and TRIS were efficient in preparing milk samples for direct analysis of suspensions, when the solution used was MEA + citric acid, respectively in a concentration of 6,0 mol.L'1 and 0,2 mol.L'1. For the Solutions of TRIS + citric acid, the ideal concentrations were, respectively, 1,5 mol.L'1 and 0,05 mol.L'1. The values found in the studies of calcium and magnesium recovery had confirmed the efficiency of the considered analytical procedures in this work. These values were 93 to 98% for calcium and 80 to 97% for magnesium. All these results were also submitted to a statisitcal treatment. The advantages related to the procedures applied in this work are: use of commercial and cheap reagents, reduced time for sample preparing (2 minutes for the Solutions with amino mixtures and 8 minutes for the acid digestion using mircrowavesXVIII irradiation), little possibilities of contamination, little losses of analitos and the use of analytical curves with watery standard Solutions. The investigated analytical procedures can be implemented in routine analysis and the choice of the method must consider the available equipment in the laboratory and the experience of the analyst.